KETERAMPILAN PEMECAHAN MASALAH, BERPIKIR KREATIF, DAN PENALARAN PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA VISUAL [PROBLEM SOLVING, CREATIVE THINKING, AND REASONING SKILLS IN LEARNING MATHEMATICS USING VISUAL LEARNING MEDIA] - Dhesy Adhalia; Nancy Susianna (Polyglot, 2021)
Problem solving, creative thinking, and reasoning skills are important skills for students to master to solve various problems that they will face in the future. However, there are still many students that have relatively low ability levels performing these three skills. To improve students' abilities in these three skills, teachers can use learning strategies that incorporate visual learning media. The problem identified in a class of third graders at a public elementary school (SDN 01) in Jagakarsa was the lack of use of learning media in the learning process in the classroom so students' ability in all three skills was less developed. A research study was conducted to determine the increase in problem solving skills, creative thinking skills, and reasoning skills of third grade students at SDN 01 Jagakarsa in math subjects after being taught using instructional media. Data sources were obtained from students' test scores before and after being taught using visual learning media. Based on the N-gain calculation and data analysis using inferential statistics, results showed that the use of visual learning media can improve students' ability to solve problems, think creatively, and reason, especially in mathematics subjects.BAHASA INDONESIA ABSTRACT: Keterampilan memecahkan masalah, berpikir kreatif, dan menalar merupakan keterampilan yang penting dikuasai siswa untuk menyelesaikan bermacam persoalan yang akan dijumpainya kelak di masa yang akan datang. Kenyataannya masih banyak ditemui siswa dengan kemampuan ketiga keterampilan tersebut yang tergolong rendah. Untuk meningkatkan kemampuan siswa pada ketiga keterampilan tersebut, guru dapat menggunakan strategi pembelajaran menggunakan media pembelajaran. Masalah yang teridentifikasi di kelas III SDN 01 Jagakarsa adalah masih kurangnya penggunaan media pembelajaran yang digunakan dalam proses pembelajaran di kelas, sehingga kemampuan siswa dalam ketiga keterampilan tersebut kurang berkembang. Oleh karena itu dilakukan penelitian untuk mengetahui peningkatan kemampuan memecahkan masalah, berpikir kreatif, serta menalar siswa kelas III SDN 01 Jagakarsa pada mata pelajaran matematika setelah diajarkan dengan menggunakan media pembelajaran. Sumber data didapat dari nilai siswa sebelum dan sesudah diajarkan dengan menggunakan media pembelajaran visual. Berdasarkan hasil perhitungan N-gain dan analisis data menggunakan statistik inferensial didapat kesimpulan bahwa penggunaan media pembelajaran visual dapat meningkatkan kemampuan siswa dalam memecahkan masalah, berpikir kreatif, dan menalar secara keseluruhan khususnya pada mata pelajaran matematika.